Depressive symptoms and adherence to treatment among people with type 2 diabetes mellitus - Braz, Juciene Matos; Silva, Mônica Rodrigues; Gois, Cristiane Franca Lisboa; Braz, Tércio Matos; Santos, Valmira dos; Silva, Lausimary Araújo São Mateus (Rev Rene, 2012)
This study aimed to verify the association between depressive symptoms and socio-demographic and clinical variables, and the adherence to drug treatment among people with type 2 diabetes mellitus (DM2). A descriptive study developed with a sample of 145 people with DM2. We used the Beck Depression Inventory (BDI) and the Measurement of Treatment Adherence (MTA). The average age of participants was 60.4 years, 77.2% were female and 51.7% had a partner. The average BDI was 18.4 and 33.1% of the subjects presented depressive symptoms. Physical activity practice was associated to better BDI evaluation (p